Soluble interleukin-2 receptor level predicts survival in patients with follicular lymphoma treated with cyclophosphamide, doxorubicin, vincristine and prednisone chemotherapy in the rituximab era. Issue 7 (July 2014) - Procházka, Vít; Papajík, Tomáš; Faber, Edgar; Raida, Luděk; Kapitáňová, Zuzana; Langová, Kateřina; Prouzová, Zuzana; Jarošová, Marie; Indrák, Karel
Abstract This study analyzed the prognostic significance of soluble interleukin-2 receptor α (sIL-2Rα) levels in 100 prospectively enrolled patients with previously untreated follicular lymphoma. It showed that sIL-2Rα level ≥ 115 pmol/L at the time of treatment initiation correlated with a high Follicular Lymphoma International Prognostic Index-2 (FLIPI-2), bulky disease, advanced clinical stage, number of involved lymph nodes, bone marrow involvement and elevated β2-microglobulin (B2M) level. When testing all patients, sIL-2Rα ≥ 115 pmol/L was associated with significantly shorter progression-free (PFS; p < 0.03, hazard ratio [HR] 2.04) but not overall (OS; p = 0.06, HR 2.36) survival rates. Subanalysis of patients receiving cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) ± rituximab showed higher predictive power for both PFS (HR 2.75, 95% confidence interval [CI] 1.24–6.11, p = 0.01) and OS (HR 3.33, 95% CI 1.15–9.63, p = 0.02). In the whole population (n = 100), only B2M proved a significant univariate predictor (p = 0.007, HR = 2.8) of PFS. When testing patients treated with CHOP ± rituximab, sIL-2Rα was found to be the best univariate predictor for PFS among all FLIPI-2 factors (HR = 2.68, p = 0.015). Serum IL-2Rα levels may help to refine risk assessment in the modern immunotherapy era complementary to FLIPI-2 factors.